Ozone depletion: causes and solutions - Santos, Andréa de Melo; Borille, Fátima de Cássia de Athayde; Furtado , Felipe Casa Nova; Monteiro, Eliana Cristina Barreto; Campos-Takaki , Galba Maria (Seven Editora, 2023)
Since the Industrial Revolution, atmospheric carbon emissions have been more pronounced, due to the burning of fossil fuels that intensify the greenhouse effect and are currently contributing to the increase in temperature, leading to long-term global warming of the planet. The harmful interference of man on the biogeochemical cycles, especially carbon, transfers carbon from the biosphere to the atmosphere, as well as his competence in the removal of forest areas and other communities that act sequestering carbon from the atmosphere, resulting in the surplus of this gas, leading to global warming. Carbon dioxide, as well as other gases (methane, nitrous oxide, chlorofluorocarbons, and water vapor) act as greenhouse gases by seizing heat. All this heat retained in the terrestrial globe, interacts with the atmosphere and the ocean, influencing climate change, such as increased temperature and precipitation. Consequently, there is an increase in the temperature of the planet that has been melting the glaciers and increasing the sea level. Island nations and littoral countries are more exposed to feeling the consequences of rising sea levels. Another consequence of the imbalance of the greenhouse effect is related to the emergence and aggravation of some diseases such as skin cancer, and cataracts, among others, requiring the incessant search for solutions through scientific and technological development, combined with policies to minimize the current environmental crisis.DOI:https://doi.org/10.56238/alookdevelopv1-050